Zero defect: evaluation on implementation in power semiconductor department of Infineon Malacca / Azwani Mohamad - Mohamad, Azwani (Faculty of Business and Management, 2006)
According to the topic chosen, Zero Defect is one of the quality tools that is been implemented in Infineon Technologies Malacca. Intineon Technologies has been trying to achieve Zero Defect in their production in order to compete in the rapid technology changing of Semiconductor market. Thus, from applying Zero Defect, not only it will increase the quality of their production, but also it can help to increase production and reduce cost. Research objectives for this study undertaken are to determine the most frequent Zero Defect activities been done in Power Semiconductor Department, to identify the major contributors of Zero Defect, to determine are there any relationship between all the predicted variables and Zero Defect, to determine the need of these quality tools implementation among Power Semiconductor (PS) department employees, and also to recommend improvements or solutions in this research The scope of study is mainly focusing on the evaluation of Zero Defect implementation in the PS Production Department of Infineon Technologies Malacca There are 6 hypothesis testing, which is focusing on the testing on the direct relationship between the dependent variable (Zero Defect) and all its independent variables (all the predicted quality tools that contribute to Zero Defect). Then the data has been collected from 250 respondents which has been given a set of 60 questions to be answered accordingly. From these data then it has been analyze and interpetate accordingly.